SiKurban: A Web-Based One-Time-Use QR Code System Using LCG for Real-Time Duplicate-Claim Prevention in Qurban Meat Distribution - Farras Fathin Naufal; Dedy Irfan; Delvi Asmara (Sagamedia Teknologi Nusantara, 2026)
Paper coupons used for qurban (Islamic animal sacrifice) meat distribution are vulnerable to loss, physical damage, forgery, and repeated redemption. At Surau Kumango Pasa Gadang in Padang, West Sumatra, the 2025 process involved 448 coupons, 56 participants, eight animals, and 20 committee members. This study designed and functionally evaluated SiKurban, a web application that replaced paper-only verification with one-time-use QR codes and real-time duplicate-claim prevention. Development followed the Waterfall model using Laravel and MySQL. Initial token values were generated with a Linear Congruential Generator (LCG) using the Numerical Recipes parameters (a = 1,664,525; c = 1,013,904,223; m = 2³²), checked for uniqueness in the database, and signed with HMAC-SHA256. During scanning, the application verified the token and its status, then committed the distribution record, the scan log, and the irreversible transition to “used” within a single locked database transaction. Developer-executed black-box testing on 1 July 2026 covered 33 scenarios (28 positive and five negative or edge cases). All scenarios produced the specified outputs, including rejection of reused and unregistered codes. The findings demonstrated developer-verified functional conformance of this single-site prototype under the specified test conditions; they do not establish independent validation or field effectiveness. The 13 non-functional requirements, usability, user acceptance, security resistance, scalability, cost, and performance under unstable connectivity remain to be evaluated by committee members or independent testers during live or high-fidelity distribution.